Fire safety aspects of refuge floors in supertall buildings with computational fluid dynamics - Chow, Cheuk Lun; Chow, Wan Ki (Journal of Civil Engineering and Management, 2009)
High‐rise buildings in many big cities in the Far East, including Hong Kong, call for refuge floors as a matter of both practicality and compliance with regulations. Even though many countries’ fire codes are not clear in spelling out the necessity for refuge floors, it is accepted within construction that such floors are essential in resisting fire, allowing users a means of escape and allowing emergency services a means of access to stricken buildings. This paper discusses the reasons behind providing refuge floors, while also considering related fire safety provisions, such as their enclosure behind fire‐resistant construction or the protection of their openings behind a water curtain. Our discussion takes a tall building with balconies as a test example of refuge floors, running a hazard assessment based on Computational Fluid Dynamics assuming a fire of the broadly accepted level of 2 MW. The paper concludes that the design of the building’s façade finally determines whether or not a refuge floor and associated fire safety provisions, such as a water curtain, can be waived. As the flat modelled used to store a high amount of combustibles up to 1135 MJm−2, the breaking of large area of glass window could lead to a major conflagration. The consequences of a scenario with a fire of 25 MW are also discussed. Santrauka Daugelio Tolimųjų Rytų didžiųjų miestų aukštuminiuose pastatuose, taip pat ir Honkongo, reikalingi saugos aukštai, paisant praktiškumo ir atitikimo reikalavimus. Netgi jei daugelio šalių gaisrinės saugos normos aiškiai nereglamentuoja būtinybės įrengti saugos aukštų, konstrukciniu požiūriu tokie aukštai yra būtini gaisrinei saugai, užtikrinant pastato naudotojams evakuacijos galimybę ir avarinėms tarnyboms patekimą į pastatą. Straipsnyje aptariamos saugos aukštų įrengimo priežastys, taip pat įvertinamos susijusios tokios gaisrinės saugos priemonės, kaip atsparių ugniai konstrukcijų įrengimas arba angų apsauga vandens užuolaida. Nagrinėjamas aukštuminis pastatas su balkonais, kaip eksperimentinis saugos aukštų pavyzdys, įvertinant pavojų. Tai daroma naudojant skysčių dinamikos modeliavimą ir plačiai pripažintą 2 MW galios gaisrą. Straipsnyje daromos išvados, kad pastato fasado projektiniai sprendiniai daro įtaką, ar saugos aukštai ir susijusios tokios gaisrinės saugos priemonės, kaip vandens užuolaida, gali būti nenumatomi. Jei pastate numatoma saugoti daug degiųjų medžiagų viršijant 1135 MJm–2 gaisro apkrovą, didelio ploto langų išdužimas gali veikti visuminį užsidegimą. Aptariami ir 25 MW galios gaisro scenarijaus padariniai. First Published Online: 14 Oct 2010 Reikšminiai žodžiai: saugos aukštas, ypač aukšti pastatai, evakuacija, gaisrinės saugos priemonės.